Pendampingan Program Jalin Matra Feminisasi Kemiskinan Propinsi Jawa Timur Tahun 2015 Di Desa Nglanduk Kec Wungu Kab Madiun - Nanang Cendriono (Universitas Muhammadiyah Ponorogo, 2017)
East Java Government is committed to run sustainable development which is centered on society, especially the pro-poor-people (pro-poor growth) and gender mainstreaming. It is stated in the medium-term Region development plan period 2015-2019, with East Java development vision “Jawa Timur Lebih Sejahtera, Berkeadilan, Mandiri, Berdaya Saing, dan Berakhlak” and mission “Makin Mandiri Sejahtera Bersama Wong Cilik”. In order to realize the concept, the government designs a program to take in hand women’s poverty, especially for households in the manner of Kepala Rumah Tangga Perempuan (KRTP) through Feminism Poverty Reduction (FPR) program. The program is not only as a short-term effort to provide assistance to KRTP but also as an ongoing program in order to anticipate poverty trap on KRTP. Desa Nglanduk, based on Basis Data Terpadu (BDT) Tim Nasional Percepatan Penanggulangan Kemiskinan (TNP2K) is the lowest 10% (decile 1) household welfare with female as the head of household. According to the data, prospective targets KRTP to implementate the Feminism Poverty Reduction (FPR) is as much as 20 households. Therefore, the existence of program assistant will help the process zero in on. The proposal of disbursement Special Financial Assistance Feminism Proverty Reduction Jalin Matra program East Java 2015 became one of instrument control which is expected capable to solve the problems particularly women’s poverty in the family level.